Do Facilities Affect Tourists’ Satisfaction at Natural Tourist Attraction? A Case at Tegenungan Waterfall in Bali - Febriyana, Gede Muna Satya; Suprastayasa, I G.N. Agung; Darmiati, Made (Institut Pariwisata Trisakti, 2020)
Research on tourist satisfaction has been a topic of interest for many academicians. This study aimed to examine the effect of tourist facilities on tourist satisfaction at the natural attractions of Tegenungan waterfall, Bali. The sampling method used was accidental sampling with 100 samples collected in 5 days. Analysis of the data used is descriptive analysis and simple linear regression analysis. The results of the study indicate that the tourist facility variable has a significant effect on tourist satisfaction. T test results show that the tourist facilities (X) significantly affect tourist satisfaction (Y) at the natural attractions of Tegenungan waterfall, Bali. It is expected that the quality of existing tourist facilities can be improved so that it can have a positive impact on the satisfaction of tourists visiting the waterfall. Keywords: tourist facilities, tourist satisfaction, natural tourist attraction,